A case of Tinea Faciei caused by Trichophyton benhamiae: first report in China - Tan, Jingwen (BMC Infect Dis, 2020)
BACKGROUND: Trichophyton benhamiae is a zoophilic dermatophyte that can cause tinea in humans and animals. Lesions caused by T. benhamiae tend to be highly inflammatory, and patients are often infected by animals or other patients infected with T. benhamiae. In this paper, we report the first case of tinea faciei caused by T. benhamiae in a Chinese girl who might be transmitted from a fox. CASE PRESENTATION: A 4-year-old girl from HaiNing city developed an itchy, erythematous, and annular plaque on her right face for the past 2 months. Before the lesion appeared, she was in close contact with the fur of a fox for almost 1 week. Septate hyaline hyphae were detected by direct mycological examination of the scales. Cultures grew on Sabouraud’s dextrose agar (SDA) at 26 °C for 2 weeks revealed the presence of T. mentagrophytes. A molecular sequencing test confirmed that the isolate was consistent with reference strains to T. benhamiae. Then, the diagnosis of tinea faciei due to T. benhamiae was made. Treatment with terbinafine (oral 125 mg/d) and sertaconazole nitrate cream (topical, twice daily) for 4 weeks was initiated and achieved significant improvement of the skin lesions. CONCLUSIONS: This rare dermatophytosis case highlights the importance of ITS sequencing in helping to recognize rare pathogenic fungi that can be easily misdiagnosed with a conventional morphological diagnosis.